On the convergence of solutions of certain inhomogeneous fourth-order differential equations - Tunc, E. (Український математичний журнал, 2010)
The main purpose of this paper is to give sufficient conditions for the convergence of solutions of a certain class of fourth-order nonlinear differential equations using Lyapunov’s second method. Nonlinear functions involved are not necessarily differentiable, but a certain incrementary ratio for a function h lies in a closed subinterval of the Routh–Hurwitz interval. Головною метою статті є наведення достатніх умов для збіжності розв'язків деякого класу нелінійних диференціальних рівнянь четвертого порядку з використанням другого методу Ляпунова. Розглядувані нелінійні функції необов'язково диференційовні, але функція h задовольняє деяке відношення приростів, що лежать у замкненому підінтервалі інтервалу Рута-Гурвіца.